The Search for Biomarkers in Hereditary Angioedema - Kaplan, Allen P.; Maas, Coen (Frontiers in Medicine, 2017)
The unpredictable nature of attacks of tissue swelling in hereditary angioedema requires the identification of reliable biomarkers to monitor disease activity as well as response to therapy. At present, one can assess a C4 level (by ELISA) to assist in diagnosis but neither C4 nor C1 inhibitor levels reflect clinical course or prognosis. We will here review a collection of plasma proteins involved in blood coagulation, fibrinolysis, and innate immunity (Figure 1). A main focus is those proteins that are key to the formation of bradykinin (BK); namely, factor XII, plasma prekallikrein/kallikrein, high-molecular weight kininogen, and BK itself since overproduction of BK is key to the disease. Considerations include new approaches to measurement of active enzymes, ELISA methods that may supersede SDS gel analysis of bond cleavages, and examples of changes outside the BK cascade that may reflect when, where, and how an attack of swelling is initiated. We will discuss their usefulness as biomarker candidates, with pros and cons, and compare the analytical methods that are being developed to measure their levels or activity.